Mental Health Assessment: A Comparison between Different Completely Edentulous and Dentate Patients - Nadira A Hatim; Monia MN Kandil; Elham Kh Al-Jamas (University of Mosul, College of Dentistry, 2008)
Aims: To aid the dentist, in a more precise method for the mental health assessment of edentulous patients, and isolates those who refuse complete denture wearing for psychological reasons. Materials and methods: The study was conducted during the period from July 2004 to November 2005. One hundred members with especial criteria were agreed to participate in this study. They were collected randomly from Dental College of Mosul University and Dental Health Center at Mosul city. The members were asked to answer the Mental Health Questionnaires. Results: It was found that mental health score decreased with females especially who refused the prosthodontic treatment, also groups with low educational and financial levels at same group. Members that received their prosthodontic treatment at the Dental Collage with age between (55-64) years old seamed to be achieved a highest level within the Mental Health Scale. Finally the members with high anxiety tendency, showed less mental health scores. Conclusions: The completely edentulous who refused the prosthodontic treatment, especially females, low educational and financial groups achieved the minimum scores with Mental Health Scale.